Two groups of cocirculating, epidemic clostridiodes difficile strains microdiversify through different mechanisms - Murillo, Tatiana (2018)
Clostridiodes difficile strains from the NAPCR1/ST54 and NAP1/ST01 types have caused outbreaks despite of their notable differences in genome diversity. By comparing whole genome sequences of 32 NAPCR1/ST54 isolates and 17 NAP1/ST01 recovered from patients infected with C. difficile we assessed whether mutation, homologous recombination (r) or nonhomologous recombination (NHR) through lateral gene transfer (LGT) have differentially shaped the microdiversification of these strains. The average number of single nucleotide polymorphisms (SNPs) in coding sequences (NAPCR1/ST54 ¼ 24; NAP1/ST01 ¼ 19) and SNP densities (NAPCR1/ST54 ¼ 0.54/kb; NAP1/ST01 ¼ 0.46/kb) in the NAPCR1/ST54 and NAP1/ST01 isolates was comparable. However, the NAP1/ST01 isolates showed 3 higher average dN/dS rates (8.35) that the NAPCR1/ST54 isolates (2.62). Regarding r, whereas 31 of the NAPCR1/ST54 isolates showed 1 recombination block (3,301–8,226 bp), the NAP1/ ST01 isolates showed no bases in recombination. As to NHR, the pangenome of the NAPCR1/ST54 isolates was larger (4,802 gene clusters, 26% noncore genes) and more heterogeneous (644 6 33 gene content changes) than that of the NAP1/ST01 isolates (3,829 gene clusters, ca. 6% noncore genes, 129 6 37 gene content changes). Nearly 55% of the gene content changes seen among the NAPCR1/ST54 isolates (355 6 31) were traced back to MGEs with putative genes for antimicrobial resistance and virulence factors that were only detected in single isolates or isolate clusters. Congruently, the LGT/SNP rate calculated for the NAPCR1/ST54 isolates (26.8 6 2.8) was 4 higher than the one obtained for the NAP1/ST1 isolates (6.8 6 2.0). We conclude that NHR-LGT has had a greater role in the microdiversification of the NAPCR1/ST54 strains, opposite to the NAP1/ST01 strains, where mutation is known to play a more prominent role.